Optimal conditions for synthesis of long complementary DNA product with Moloney murine leukemia virus. - Van Beveren, C (J Virol, 1979)
Studies are described on the interrelationships between divalent metals, dNTP's and PPi in determining the properties of complementary DNA (cDNA) product from the in vitro reverse transcriptase reaction with detergent-treated Moloney murine leukemia virus. In spite of the several-fold greater amount of cDNA product with Mn2+ than with Mg2+, net yield of high-molecular-weight cDNA was much greater with Mg2+ thant with Mn2+. This held true, as well, for the reactions containing excess dNTP or dNTP plus PPi, both of which (as has been reported for Mg2+) promote synthesis of high-molecular-weight cDNA product. Hif total dNTP concentration remained important for maximum high-molecular-weight product with Mg2+ and was not replaced by simply providing dNTP in excess over Mg2+. Under the conditions tested here, addition of PPi did not further increase cDNA product size with Mg2+ when compared with dNTP in excess over Mg2+. Extent of degradation of the RNA template during the incubations was correlated with the size of cDNA product.